Motivation and self-regulated strategy use: Relationships to primary school students’ English writing in Hong Kong - Bai, Barry; Guo, Wenjuan (Language teaching research : LTR, 2021)
This study was to examine the individual differences in primary school students’ motivation (i.e. growth mindset, self-efficacy, and interest), self-regulated learning strategy use in English writing and the relationships between motivation, strategy use and English writing competence. Participants were 523 4th grade primary school students in Hong Kong. Although the findings showed a general pattern that the high achievers reported higher levels of motivation (i.e. growth mindset, self-efficacy, and interest) and self-regulated learning (SRL) strategy use than the average achievers, who in turn outperformed the low achievers, all the students showed quite a low level of interest in English writing. Interestingly, motivation impacted SRL strategy use very differently for students of different writing competence groups on the whole. Three-group Structural Equation Modelling (SEM) suggested that growth mindset had the strongest and most significant correlations with all students’ use of SRL strategies. However, interest and self-efficacy had different relationship patterns with SRL strategy use among the high, average and low achievers. Interest had no significant relations with the high achievers’ SRL strategy use, while self-efficacy had no significant relations with the low achievers’ SRL strategy use. Implications for English teachers to improve differentiated instruction are discussed.